New cave-dwelling Plakina (Plakinidae, Homoscleromorpha, Porifera) from Martinique Island (French Antilles) - Grenier, Marie; Ruiz, Cesar; Lage, Anaira; Perez, Thierry (Zootaxa, 2020)
Knowledge of homoscleromorph sponge biodiversity has greatly improved during the last decade thanks to the increasing use of integrative taxonomy and extensive exploration of remote ecosystems. Indeed, recently described species have mostly been small sponges living in dark and near-impenetrable habitats. This work integrates morphological, cytological, ecological and molecular data to describe a new species belonging to the Plakina genus. Plakina doudou sp. nov. was found first during close inspection of photographs taken previously in a submarine cave on Martinique Island, where several new species had already been revealed. The new species lives in syntopy with P. arletensis. It is thinly encrusting, whitish in vivo, and its skeleton harbors a unique composition of diods, triods, monolophose triods and monolophose, dilophose and trilophose calthrops. Sequencing of a portion of the mitochondrial gene cox-1 indicates that the new species belongs to a well-supported clade containing the Mediterranean P. crypta and P. trilopha. However, at the time of publication of this work, we have not yet managed to identify synapomorphies that would support the different clades of Plakina. This genus includes a total of 39 species to date, of which 10 have been recorded in the Western Tropical Atlantic, and 4 in Caribbean submarine caves.